Method for manufacturing semiconductor device, silica sol, method for producing same, and polishing composition

By aging treatment in the active silica acid solution and multi-step stirring and dropping reaction, a polydispersed silica sol with a wide SiO2 particle size distribution was prepared, which solved the problems of long preparation period of silica sol and low mechanical polishing effect in the existing grinding composition, and achieved efficient mechanical grinding effect and polishing rate.

CN119612522AActive Publication Date: 2025-03-14DINGZE (XIANTAO) NEW MATERIALS TECHNOLOGY CO LTD +3
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510163022.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-14
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

In the existing grinding compositions, monodispersed and large-particle silicon sols have problems such as long preparation period and low mechanical polishing effect, which cannot meet the needs of high-precision polishing.

Method used

By aging in an active silica acid solution, adjusting the pH value and performing multi-step stirring and dropping reactions, a polydispersed silica sol with a wide SiO2 particle size distribution was prepared for the grinding composition.

Benefits of technology

The particle size distribution of the silica sol has been realized from irregular to ordered normal distribution, and the mechanical grinding effect and polishing rate of the polishing composition are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612522A_ABST
    Figure CN119612522A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of a semiconductor device, silica sol, a preparation method of the silica sol and a composition for grinding, and relates to the technical field of silica sol preparation. The method for manufacturing a semiconductor device includes a step of polishing the surface of a semiconductor wafer with a polishing composition, the polishing composition including a silica sol, and the method for preparing the silica sol includes: preparing an active silicic acid solution from a cationic resin; adjusting the pH value of the active silicic acid solution to be neutral, and aging the active silicic acid solution at high temperature; adjusting the pH value of the aged silicic acid to be alkaline to obtain a silica gel matrix seed crystal solution; and dropwise adding an active silicic acid solution to obtain the silica sol with wide particle size distribution. The silica sol provided by the invention has very wide SiO2 particle size distribution and is ordered normal distribution, when the silica sol is applied to the composition for grinding, large-particle-size SiO2 and small-particle-size SiO2 are matched with each other, the friction coefficient between the silica sol and a parabolic object is large, the polishing rate during copper polishing can be remarkably increased, and a very good mechanical grinding effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of silica sol preparation, and in particular to a method for manufacturing a semiconductor device, silica sol and a preparation method thereof, and a polishing composition. Background Art

[0002] With the rapid development of integrated circuit technology, the surface quality requirements of the substrate materials used are getting higher and higher. Due to the reduction in device size and the reduction in the focal depth of optical lithography equipment, the wafer surface is required to have an acceptable resolution flatness of nanometer level. Chemical mechanical polishing (CMP) technology is currently recognized as the most effective means of processing silicon wafer surface flatness, and "SiO 2 "Chemical mechanical polishing liquid" is the most used and effective important raw material.

[0003] The current mainstream grinding compositions use monodisperse, large-particle silica sol as abrasives, but such abrasives often have problems such as long preparation cycles and low mechanical polishing effects, and cannot meet the polishing requirements of most objects being polished. Therefore, how to optimize silicon abrasives to reduce the cost and energy consumption of grinding compositions has received widespread attention in the semiconductor-related industry. In order to overcome the above problems, many scientific researchers have made many effective attempts. CN101626979A provides a slender silicon dioxide particle and a preparation method thereof, which has a large friction coefficient and a high polishing rate during polishing. However, the slender SiO 2 The particles are also easy to scratch and damage the surface of the polishing material. CN106044786B provides a preparation process of polydisperse large-particle silica sol, which uses two monodisperse small-particle silica sols of different particle sizes as seeds, and then drips active silicate solution under alkaline conditions to complete the process of particle size growth; however, the process takes up to 20-30 hours and the reaction conditions are relatively complicated. Summary of the invention

[0004] The present application provides a method for manufacturing a semiconductor device, a silica sol and a preparation method thereof, and a polishing composition. The silica sol prepared by the preparation method of the silica sol has a wide range of SiO 2 The wide particle size distribution is an orderly normal distribution. After the silica sol is prepared into a grinding composition, the large particle size SiO 2 With small particle size SiO 2 They cooperate with each other, have a large friction coefficient with the thrown object, and can achieve a good mechanical grinding effect.

[0005] In a first aspect, the present application provides a method for manufacturing a semiconductor device. The invention comprises a process of grinding the surface of a semiconductor wafer using a grinding composition, wherein the grinding composition comprises silica sol, and the preparation method of the silica sol comprises the following steps: S1: exchanging the diluted water glass and the cationic resin to obtain an active silicate solution with a pH value of 2.0-2.5; S2: adding a strong alkaline aqueous solution to the active silicic acid solution, adjusting the pH value to 7-8, heating to 60-80° C., and keeping the temperature for a first preset time, cooling and filtering through a microporous filter membrane to obtain an aged silicic acid solution; S3: adding a strong alkaline aqueous solution to the aged silicic acid solution, adjusting the pH value to 11-11.5, stirring thoroughly, heating to boiling and keeping the temperature for a second preset time to obtain a silica gel matrix seed solution; S4: heating the silica gel matrix seed solution to 95-100° C. under stirring, and dripping the active silicic acid solution at a preset dripping rate to obtain silica sol.

[0006] In the above technical scheme, the pH of the active silicate solution is adjusted to neutral to age the active silicate solution. The aged silicate is prone to undergo dehydration condensation reaction to form large-particle silicon abrasive agglomerates, and small crystals are continuously produced while the old crystal seeds grow, thereby increasing the particle size of the silica sol and making the particle size distribution inconsistent, thereby obtaining a polydisperse silica sol with a wide particle size distribution and a larger average particle size.

[0007] In a second aspect, the present application provides a method for preparing a silica sol, comprising the following steps: S1: exchanging the diluted water glass with the cationic resin to obtain an active silicate solution with a pH value of 2.0-2.5; S2: adding a strong alkaline aqueous solution to the active silicic acid solution, adjusting the pH value to 7-8, heating to 60-80° C., and keeping the temperature for a first preset time, cooling and filtering through a microporous filter membrane to obtain an aged silicic acid solution; S3: adding a strong alkaline aqueous solution to the aged silicic acid solution, adjusting the pH value to 11-11.5, stirring thoroughly, heating to boiling and keeping the temperature for a second preset time to obtain a silica gel matrix seed solution; S4: heating the silica gel matrix seed solution to 95-100° C. under stirring, and dripping the active silicic acid solution at a preset dripping rate to obtain silica sol.

[0008] In some possible implementations, the first preset time in the step S2 is 1-5 hours, and the viscosity of the aged silicic acid solution is 5-17 mPa·s.

[0009] In some possible implementations, the first preset time is preferably 3-5 hours, and the pH value is preferably 7.5-8.

[0010] In some possible implementations, the preset dripping rate in step S4 is 10-50 g / min.

[0011] In some possible implementations, the second preset time in step S3 is 1-3 hours, the reaction pressure is 140 kPa, and the SiO 2 The particle size of the seed crystal is 10-30 nm, the temperature of heating the silica gel matrix seed crystal solution is 120-150° C., and the heating method is steam heating.

[0012] In some possible embodiments, the cationic resin in step S1 is a strong acid sulfonic acid resin, and the strong alkali aqueous solution in steps S2 and S3 can be selected from one or more of sodium hydroxide, ammonia, triethanolamine, ethylenediamine, sodium carbonate, etc. In a third aspect, the present application provides a silica sol, including a silica sol obtained by the preparation method described in any one of the embodiments of the first aspect.

[0013] In some possible implementations, the silica sol has a particle size of 10-150 nm and a viscosity of 3.0 mPa·s to 6.0 mPa·s.

[0014] In a fourth aspect, the present application provides a polishing composition comprising water and the silica sol described in any one embodiment of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is an electron microscope picture of the silica sol prepared in Example 1; Figure 2 This is a picture of the particle size distribution of the silica sol prepared in Example 1; Figure 3 This is an electron microscope picture of the silica sol prepared in Example 2; Figure 4 This is a picture of the particle size distribution of the silica sol prepared in Example 2; Figure 5 This is an electron microscope picture of the silica sol prepared in Example 3; Figure 6 This is a picture of the particle size distribution of the silica sol prepared in Example 3; Figure 7 This is an electron microscope picture of the silica sol prepared in Example 4; Figure 8 This is a picture of the particle size distribution of the silica sol prepared in Example 4; Fig. 9 This is an electron microscope picture of the silica sol prepared in Comparative Example 1; Fig.10 This is a picture of the particle size distribution of the silica sol prepared in Comparative Example 1; Fig.11This is an electron microscope picture of the silica sol prepared in Comparative Example 2; Fig.12 This is a picture of the particle size distribution of the silica sol prepared in Comparative Example 2; Fig.13 This is an electron microscope picture of the silica sol prepared in Comparative Example 3; Fig.14 This is a picture of the particle size distribution of the silica sol prepared in Comparative Example 3; Fig.15 This is an electron microscope picture of the silica sol prepared in Comparative Example 4; Fig.16 This is a picture of the particle size distribution of the silica sol prepared in Comparative Example 4. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0017] It should be noted that the following embodiments are examples of the present application and are only used to illustrate the present application, but not to limit the present application. Other combinations and various improvements within the concept of the present application may be made without departing from the subject matter or scope of the present application.

[0018] The following is a detailed description of the method for manufacturing a semiconductor device, the silica sol and its preparation method, and the polishing composition provided in the present application.

[0019] The method for manufacturing a semiconductor device according to an embodiment of the present application includes a step of grinding a surface of a semiconductor wafer using a grinding composition, wherein the grinding composition includes silica sol, wherein the method for preparing the silica sol includes the following steps: S1: exchanging the diluted water glass with the cationic resin to obtain an active silicate solution with a pH value of 2.0-2.5; S2: adding a strong alkaline aqueous solution to the active silicic acid solution, adjusting the pH value to 7-8, heating to 60-80° C., and keeping the temperature for a first preset time, cooling and filtering through a microporous filter membrane to obtain an aged silicic acid solution; S3: adding a strong alkaline aqueous solution to the aged silicic acid solution, adjusting the pH value to 11-11.5, stirring thoroughly, heating to boiling and keeping the temperature for a second preset time to obtain a silica gel matrix seed solution; S4: heating the silica gel matrix seed solution to 95-100° C. under stirring, and dripping the active silicic acid solution at a preset dripping rate to obtain silica sol.

[0020] The silica sol preparation method provided in the present application realizes the regulation of particle size and morphology by the method of aging crystal seeds, and the process is short and the method is simple. Before forming the silica matrix seed solution, the pH of the active silica acid solution is adjusted to neutral, so that the active silica acid solution is aged, so that when the silica sol is subsequently formed, the aged silica acid solution can continuously produce small crystal seeds, so that the old crystal seeds grow and continuously produce small crystal seeds, thereby obtaining a silica sol with a wide particle size distribution. Since silica acid is prone to gelation when it stays for too long under pH neutral conditions, it is necessary to quickly add a strong alkaline aqueous solution after aging for a period of time to return the pH to 11-11.5 to reach a stable state. In addition, if a small part of silica acid generates jelly-like gel blocks during aging, a filter can be used to filter out obvious large-particle gel blocks to prevent these large-particle gel blocks from reacting with the active silica acid solution in the subsequent S4, affecting the particle size distribution of the final silica sol, and significantly increasing the number of large particles of the grinding composition, reducing the application effect during the CMP process.

[0021] The silica sol provided in this application has a large average particle size and a wide SiO 2 Particle size distribution, the particle size distribution is normally distributed, such as Figure 2 , 4 , 6 and 8. After the silica sol is added with chemical reagents to prepare a grinding composition, the large-size SiO 2 With small particle size SiO 2 They cooperate with each other, have a large friction coefficient with the thrown object, and can achieve a good mechanical grinding effect.

[0022] In the present application, the strong alkali aqueous solution can be any alkali commonly used in the art, for example, one or more of sodium hydroxide, ammonia, triethanolamine, ethylenediamine, and sodium carbonate. In order to better meet the requirements of CMP semiconductor process, the strong alkali aqueous solution used in the present application is a KOH aqueous solution, which is a mixture of concentrated KOH and distilled water, with a mass fraction of 0.1-3%.

[0023] The present application does not impose any special restrictions on the type of cationic resin. The cationic resin commonly used in the art for preparing active silicate solutions can be used. Specific examples of cationic resins include sulfonic acid resins, carboxylic acid resins, or phosphonic acid resins. The cationic exchange resin of the present invention is preferably a strong acid sulfonic acid resin. Specific examples of strong acid sulfonic acid resins include polybenzene sulfonic acid resins. The ion exchange resin exchange column is a traditional fixed bed, and the exchange temperature is carried out at room temperature at 25°C.

[0024] In the present application, the silicon dioxide content of the water glass in step S1 is 5%. If the silicon dioxide content is lower than 5%, the concentration of the prepared active silicic acid solution will be too low, which will affect the SiO 2The silica content is higher than 5%, which will cause the active silicic acid solution to gel directly in the ion exchange column during ion exchange. Since the silica content of the water glass in step S1 is 5%, when the acidification, washing and exchange rate processes in the ion exchange process change, the concentration of the active silicic acid solution will also deviate and be between 4-5%.

[0025] In the present application, the first preset time in step S2 is 1-5h, and the viscosity of the aged silicic acid solution is 5-17mPa·s. Among them, the first preset time is preferably 3-5h, and the pH value is preferably 7.5-8. In step S2, it is necessary to make the viscosity of the aged silicic acid solution viscous, but it is still a liquid, in a state where it can be stirred without gel. Since silicic acid is an unstable substance, the longer it is placed, the higher the viscosity; the higher the temperature of placement, the faster the viscosity rises. Therefore, the first preset time can change with the change of heating temperature, so that the aged silicic acid solution reaches the desired state and avoids the aged silicic acid solution from condensing into a jelly state; the viscosity of the aged silicic acid solution can be controlled according to the actual situation, so that the aged silicic acid solution is in a state of high viscosity rather than condensation.

[0026] In the present application, the second preset time in step S3 is 1-3h, and the reaction pressure is 140kPa. The second preset time is 1-3h. When the second preset time is less than 1h, the aged silicic acid solution will not be in sufficient contact with the strong alkali aqueous solution, and the gelled part of the aged silicic acid solution cannot be depolymerized again into a silica gel matrix seed solution; when the second preset time is more than 3h, the silica gel matrix seed solution will be over-polymerized, and SiO 2 The seed crystals will undergo cross-linking and agglomeration to give S4 an irregular morphology of silica sol, affecting the subsequent preparation process; the reaction pressure is controlled to 140 kPa so that the heating temperature can exceed 100°C.

[0027] In the present application, the heating temperature in step S3 is 120-150°C. When the heating temperature exceeds 150°C, the heating temperature is too high, which will cause the silica matrix seed solution to overheat at the contact point with the reactor wall, causing the silica matrix seed solution to re-gel or dehydrate to form white lumps sticking to the inner wall of the reactor; when the heating temperature is lower than 120°C, the heating temperature is too low, which will extend the heating time and reduce the preparation efficiency of silica sol. The heating method is steam heating. It is understandable that the heating method can also be oil bath, electric heating, etc., preferably steam heating, which is conducive to reducing heating costs and facilitating industrialization.

[0028] In the present application, the mass fraction of the silica gel matrix seed solution in step S3 is 6-10%. The longer the active silicic acid solution is aged in step S2, the higher its pH is, and the less the amount of strong alkaline aqueous solution added in step S3 to adjust the pH is, so the mass fraction of the silica gel matrix seed solution in step S3 will deviate.

[0029] In the present application, the SiO in the silica gel matrix seed solution in step S3 is 2 The particle size of the seed crystal is between 10-30 nm.

[0030] In this application, the preset dripping rate in step S4 is 10-50 g / min. It is understandable that when the dripping rate is slow, the growth period of silica sol is longer, but the SiO 2 The morphology will be more round and the distribution will be narrower. When the dripping speed is fast, it is easier for the silicic acid solution to grow crystal nuclei, and there will be more small-sized SiO in the silica sol. 2 , SiO in silica sol 2 The morphology will tend to be more irregular. In order to better meet the requirements of CMP semiconductor process, a relatively slow silicate dripping rate is selected in the subsequent embodiments.

[0031] In the present application, compared with the conventional uniformly distributed silica sol, the particle size distribution of the silica sol in step S4 is wide, and the particle size distribution is not disordered but an orderly normal distribution. The silica sol contains both small-size SiO 2 , and there are large-particle SiO 2 , which can meet the needs of advanced CMP processes.

[0032] The silica sol provided in the present application can be used in a polishing composition. The present application also provides a polishing composition, comprising water, a pH regulator and the silica sol of any one of the above implementations. The large-particle SiO 2 With small particle size SiO 2 They cooperate with each other, have a large friction coefficient with the thrown object, and can achieve a good mechanical grinding effect.

[0033] The pH adjuster can be an organic base or an inorganic base, such as aqueous ammonia, potassium hydroxide, sodium hydroxide, sodium methoxide, sodium ethoxide, triethylamine, triethanolamine, etc. The pH adjustment range is preferably between 7 and 9.

[0034] The water is preferably deionized water.

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] Example 1

[0037] S1: Dilute water glass (Qingdao Haiwan Chemical Co., Ltd., SSL3340) with pure water to a mass fraction of 5%, stir evenly and add it into the regenerated strong acid sulfonic acid resin to perform cation exchange to obtain an active silicic acid solution with a pH of 2.3 and a silicon dioxide content of 4%.

[0038] S2: Take 500 mL of 2 wt% potassium hydroxide aqueous solution, stir and heat to 60°C, slowly add 2000 mL of 4 wt% active silicic acid solution to maintain the system pH at 7.5-8, and keep warm for 1 hour after the active silicic acid solution is added. Then pass through a 0.1 μm microporous filter membrane to obtain an aged silicic acid solution.

[0039] S3: Take 1 kg of aged silicic acid solution, add 2 wt % potassium hydroxide aqueous solution to adjust the pH to 11-11.5, stir thoroughly and heat to boiling, keep warm for 2 hours, and obtain a silica gel matrix seed solution.

[0040] S4: Take the above seed solution and add pure water to dilute it to obtain 600mL of silica seed mother solution with a mass fraction of 4wt%, stir and heat until boiling, and use a peristaltic pump to drip the active silicic acid solution at a drip rate of 10g / min. During the reaction, the pH of the entire system slowly decreases. After the addition is completed, continue to keep warm at 100℃ for 1 hour, cool naturally to room temperature, and obtain silica sol.

[0041] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 5.24 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 14 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Figure 1 It can be seen that the particle size of silica sol is distributed between 10-100nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Figure 2 It shows that silica sol has a wide range of SiO 2 Particle size distribution, and the wide particle size distribution is an ordered normal distribution.

[0042] Example 2

[0043] The reaction was carried out in the same manner as in Example 1, except that the aging time of the active silicic acid solution in step S2 was changed to 3 hours.

[0044] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 6.45 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 16 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Figure 3It can be seen that the particle size of silica sol is distributed between 10-150nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Figure 4 It shows that silica sol has a wide range of SiO 2 Particle size distribution, and the wide particle size distribution is an ordered normal distribution.

[0045] Example 3

[0046] The reaction was carried out in the same manner as in Example 1, except that the aging time of the active silicic acid solution in step S2 was changed to 5 hours.

[0047] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 7.98 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 19 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Figure 5 It can be seen that the particle size of silica sol is distributed between 10-90nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Figure 6 It shows that silica sol has a wide range of SiO 2 Particle size distribution, and the wide particle size distribution is an ordered normal distribution.

[0048] Example 4

[0049] The reaction was carried out in the same manner as in Example 2 except that the aging pH in step S2 was changed to 7.0-7.5.

[0050] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 16.31 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 21 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Figure 7 It can be seen that the particle size of silica sol is distributed between 25-105nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Figure 8 It shows that silica sol has a wide range of SiO 2 Particle size distribution, and the wide particle size distribution is an ordered normal distribution.

[0051] Comparative Example 1 This comparative example adopts a traditional method to prepare silica sol, and the parameters are basically the same as those of the aforementioned Example 2, except that the aging of the active silicic acid solution in step S2 is omitted.

[0052] In step S3, since no aging treatment was performed, the particle size of the silicon dioxide in the seed crystal was small and could not be detected by conventional particle size detection instruments. The silica sol obtained in step S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Fig. 9 It can be seen that the particle size of silica sol is distributed between 20-45nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Fig.10 Display of SiO2 in silica sol 2 The particle size distribution is narrow and is an ordered normal distribution.

[0053] Comparative Example 2 The reaction was carried out in the same manner as in Example 2 except that the pH of the aging of the active silicic acid solution in step S2 was changed to 6.5-7.0.

[0054] In step S2, the viscosity of the aged silicic acid solution could not be measured because it had gelled. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test the obtained SiO 2 The DLS particle size of the seed crystal is 26 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Fig.11 It can be seen that the particle size of silica sol is distributed between 10-110nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Fig.12 It shows that silica sol has a wide range of SiO 2 Particle size distribution, particle size distribution is a disordered distribution.

[0055] Comparative Example 3 The reaction was carried out in the same manner as in Example 2 except that the pH of the aging of the active silicic acid solution in step S2 was changed to 8.0-8.5.

[0056] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 1.64 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 11 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Fig.13It can be seen that the particle size of silica sol is distributed between 15-45nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Fig.14 Display of SiO2 in silica sol 2 The particle size distribution is narrow and is an ordered normal distribution.

[0057] Comparative Example 4 The reaction was carried out in the same manner as in Example 2, except that the aging time of the active silicic acid solution in step S2 was changed to 7 hours.

[0058] In step S2, the viscosity of the aged silicic acid solution was measured using a Brookfield DV2T viscometer from the United States and was found to be 10.72 mPa·s. In step S3, the Malvern Zetasizer PRO particle size analyzer was used to test and found that the SiO 2 The DLS particle size of the seed crystal is 18 nm. The silica sol obtained by S4 was tested using the Thermo Fisher APREO2 high-performance field emission scanning electron microscope. Fig.15 It can be seen that the particle size of silica sol is distributed between 20-140nm. Using DC24000 UHR high-precision nanoparticle size analyzer for testing, CPS Fig.16 It shows that silica sol has a wide range of SiO 2 Particle size distribution, particle size distribution is a disordered distribution.

[0059] In Examples and Comparative Examples, the physical properties of the silica sol were measured by the following methods.

[0060] The DLS particle size was tested using a Malvern Zetasizer PRO particle size analyzer; (2) The CPS particle size was tested using a DC24000 UHR high-precision nanoparticle size analyzer; (3) The SEM was tested using a Thermo Fisher APREO2 high-performance field emission scanning electron microscope.

[0061] Table 1 Physical property measurement results of Examples 1-4 and Comparative Examples 1-4 Processing DLS(nm) CPS(nm) Example 1 Silicic acid aging treatment for 1h, aging pH 7.5-8.0 78.4 60.1 Example 2 Silicic acid aging treatment for 3 hours, aging pH 7.5-8.0 94.6 78.0 Example 3 Silicic acid aging treatment for 5 hours, aging pH is 7.5-8.0 84.2 68.9 Example 4 Silicic acid aging treatment for 3 hours, aging pH is 7.0-7.5 73.5 61.9 Comparative Example 1 Silicic acid is not aged 37.4 30.8 Comparative Example 2 Silicic acid aging treatment for 3 hours, aging pH 6.5-7.0 56.7 49.5 Comparative Example 3 Silicic acid aging treatment for 3 hours, aging pH is 8.0-8.5 39.2 32.0 Comparative Example 4 Silicic acid aging treatment for 7 hours, aging pH 7.5-8.0 68.7 66.9 It can be seen from Example 2, Example 4, Comparative Example 2 and Comparative Example 3 that the reaction activity of silicic acid at different pH values ​​is very different. Silicic acid contains orthosilicic acid and polysilicic acid. When its pH value changes from acidic to alkaline, polymerization-depolymerization reactions occur continuously. It can be seen from Comparative Example 2 that when the pH value of silicic acid is within the range of 6.5-7.0, the state of silicic acid is very unstable and a jelly-like gel will be formed in a very short time.

[0062] Comparing the results of Example 2 and Example 4 with Comparative Example 3, it can be seen that the aging rate of silicic acid has strict requirements on pH. In other words, it is not the case that the higher the pH, the more SiO is generated by silicic acid. 2 The faster the rate of nucleation. When the pH value of silicate is in the range of 8.0-8.5, the solubility of amorphous silica will increase significantly. This is because in addition to the monomer, silicate ions are also formed, which are in equilibrium with the solid phase. Orthosilicic acid becomes silicate ions, that is, less orthosilicic acid is used for polymerization, and the rate of nucleation formation slows down. The reaction equation is as follows: (SiO 2 ) X + 2H 2 O = Si(OH) 4 + (SiO 2 ) X-1 Si(OH) 4 + OH - = Si(OH) 5 - The CPS particle size of Comparative Example 1 and Comparative Example 3 ( Fig.10 and Fig.14 ) and SEM morphology ( Fig. 9 and Fig.13 ) are relatively close, which shows that when silicate is aged under pH>8, Si(OH) 4 The polymerization rate of SiO 2 The particle size of the crystal nucleus also does not grow substantially. Fig.11 It shows that SiO 2 The particles are seriously agglomerated, which proves that when the silicate is aged at 6.5-7.0, the Si(OH) 4 The polymerization forms a cross-linked structure.

[0063] Through Examples 1-3 and Comparative Example 4, it is known that the polymerization process of silicate is not instantaneous, but is carried out slowly and continuously. Properly extending the aging time can increase the number of crystal nuclei or make the crystal nuclei grow, so that the particle size of the silica sol obtained finally becomes larger and the distribution becomes wider. When the aging time is extended to 5 hours, the particle size of the silica sol decreases instead, because the silicate depolymerizes after polymerization. When the aging time is extended to 7 hours, the particle size decreases further, as shown by SEM. Fig.15 It can be seen that SiO 2 The particles will agglomerate. Therefore, the aging time of the active silicic acid solution is preferably 1-5 hours.

[0064] Polishing composition configuration The silica sol prepared in the present application was diluted with pure water to a silica content of 1.5 wt%, glycine 1.5%, and triazole 0.2%, and stirred evenly to prepare a slurry precursor composition. 3 The pH of the slurry precursor composition was adjusted to 7.5, and it was mixed with 1% hydrogen peroxide and immediately stirred for 10 minutes before polishing to obtain a polishing composition for polishing copper.

[0065] Polishing experiment: The polishing liquid was placed under a downward force of 2.2 psi, a platen speed of 95 rpm, a head speed of 90 rpm, and a polishing liquid feed rate of 300 mL / min. The pad model was DH3210 and the disk model was DK4705. The thickness polishing speed was calculated by measuring the mass difference before and after polishing, and the results are listed in Table 2.

[0066] Table 2 Polishing results of Examples 1-4 and Comparative Examples 1-4 Processing Polishing rate (Å / min) Example 1 The silicic acid aging treatment was carried out for 1 hour, and the aging pH was 7.5-8. 7247 Example 2 The silicic acid aging treatment was carried out for 3 hours, and the aging pH was 7.5-8. 7575 Example 3 The silicic acid aging treatment was performed for 5 hours, and the aging pH was 7.5-8. 7438 Example 4 Silicic acid aging treatment for 3 hours, aging pH is 7.0-7.5 7091 Comparative Example 1 Silicic acid is not aged 4794 Comparative Example 2 Silicic acid aging treatment for 3 hours, aging pH 6.5-7.0 4678 Comparative Example 3 The silicic acid aging treatment was carried out for 3 hours, and the aging pH was 8-8.5. 4963 Comparative Example 4 Silicic acid aging treatment for 7 hours, aging pH 7.5-8 5637 As can be seen from the table, the polishing rates of Examples 1-4 are all higher than those of Comparative Examples 1-4, among which Examples 2 and 3 are the most preferred. Compared with Comparative Example 1, the polishing rate of polished copper is significantly improved after the silica sol prepared by silicic acid aging is configured into a polishing liquid in the present application. Compared with Comparative Examples 2 and 3, after the silica sol prepared with an aging pH value between 7-8 is configured into a polishing liquid, the polishing rate of polished copper is higher than that of silica sols prepared with other pH values. Compared with Comparative Example 4, after the silica sol prepared with a silicic acid aging treatment time between 1-5h is configured into a polishing liquid, the polishing rate of polished copper is higher than that of silica sols prepared with other aging treatment times.

[0067] Although the implementation scheme of the present application has been disclosed as above, it is not limited to the applications listed in the specification and implementation scheme. It can be fully applicable to various fields suitable for the present application. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present application is not limited to the specific details and the implementation schemes shown and described herein.

Claims

1. A method for manufacturing a semiconductor device, characterized in that: The invention relates to a process of grinding a semiconductor wafer surface using a grinding composition, wherein the grinding composition comprises silica sol, and the preparation method of the silica sol comprises the following steps: S1: exchanging the diluted water glass with the cationic resin to obtain an active silicate solution with a pH value of 2.0-2.5; S2: adding a strong alkaline aqueous solution to the active silicic acid solution, adjusting the pH value to 7-8, heating to 60-80° C., and keeping the temperature for a first preset time, cooling and filtering through a microporous filter membrane to obtain an aged silicic acid solution; S3: adding a strong alkaline aqueous solution to the aged silicic acid solution, adjusting the pH value to 11-11.5, stirring thoroughly, heating to boiling and keeping the temperature for a second preset time to obtain a silica gel matrix seed solution; S4: heating the silica gel matrix seed solution to 95-100° C. under stirring, and dripping the active silicic acid solution at a preset dripping rate to obtain silica sol.

2. A method for preparing silica sol, characterized in that: The steps include: S1: exchanging the diluted water glass with the cationic resin to obtain an active silicate solution with a pH value of 2.0-2.5; S2: adding a strong alkaline aqueous solution to the active silicic acid solution, adjusting the pH value to 7-8, heating to 60-80° C., and keeping the temperature for a first preset time, cooling and filtering through a microporous filter membrane to obtain an aged silicic acid solution; S3: adding a strong alkaline aqueous solution to the aged silicic acid solution, adjusting the pH value to 11-11.5, stirring thoroughly, heating to boiling and keeping the temperature for a second preset time to obtain a silica gel matrix seed solution; S4: heating the silica gel matrix seed solution to 95-100° C. under stirring, and dripping the active silicic acid solution at a preset dripping rate to obtain silica sol.

3. The preparation method according to claim 2, characterized in that: The first preset time in the step S2 is 1-5 hours, and the viscosity of the aged silicic acid solution is 5-17 mPa·s.

4. The preparation method according to claim 3, characterized in that: The first preset time is preferably 3-5 hours, and the pH value is preferably 7.5-8.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The preset dripping rate in the step S4 is 10-50 g / min.

6. The preparation method according to any one of claims 2 to 4, characterized in that: The second preset time in the S3 step is 1-3h, the reaction pressure is 140kPa, the particle size of the SiO2 seeds in the silica gel matrix seed solution is 10-30nm, the heating temperature of the silica gel matrix seed solution is 120-150°C, and the heating method is steam heating.

7. The preparation method according to any one of claims 2 to 4, characterized in that: The cationic resin in step S1 is a strong acid sulfonic acid resin, and the strong alkali aqueous solution in steps S2 and S3 can be selected from one or more of sodium hydroxide, ammonia water, triethanolamine, ethylenediamine, and sodium carbonate.

8. A silica sol, characterized in that: The invention comprises a silica sol obtained by the preparation method according to any one of claims 2 to 7.

9. The silica sol according to claim 8, characterized in that The particle size of the silica sol is 10-150 nm.

10. A polishing composition, characterized in that: Including the silica sol described in claim 8 or 9.

Citation Information

Patent Citations

  • Polydisperse large-particle-size silica sol and preparing method thereof

    CN106044786A

  • Silica sol and preparation method thereof

    CN110194458A

  • Method for preparing ultra-large-particle-size high-concentration silica sol from water glass

    CN111732107A

  • Method for preparing silica sol with large particle size and narrow distribution

    CN114249330A

  • Preparation method of high-purity nano silica sol with controllable particle size

    CN117049553A